Acrylonitrile water-based binder for lithium-ion batteries and preparation process thereof
By using the preparation process of acrylonitrile water-based adhesive in lithium-ion batteries, the environmental pollution and insufficient bonding strength of traditional adhesives are solved, and higher bonding strength, mechanical strength and electrochemical properties are achieved. Extend the service life of lithium-ion batteries.
Patent Information
- Application Number
- CN202411157306.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The adhesives of traditional lithium-ion batteries have problems such as environmental pollution, insufficient bonding strength, poor compatibility with electrode materials, poor stability and poor electrochemical performance, which limits their application in lithium-ion batteries.
Using the preparation process of acrylonitrile water-based binder, the reaction is carried out under specific conditions through raw materials such as 2-chloro-5-nitrotrifluorotoluene, reduced iron powder, etc., to form a bond containing a large number of carboxyl groups, amide groups and quaternary ammonium groups. Catheter.
It improves the bonding force between the adhesive and the electrode material, enhances the mechanical strength and stability of the electrode, improves the conductivity and electrochemical properties of the electrode, and extends the cycle life and rate performance of the lithium-ion battery.
Smart Images

Figure BDA0005005372270000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to an acrylonitrile aqueous binder for lithium ion batteries and a preparation process thereof. Background Art
[0002] At present, graphite, as the main negative electrode material for commercial lithium-ion batteries, has a theoretical specific capacity of only 370mAh / g, which cannot meet the needs of high energy storage devices. Silicon negative electrode has a high theoretical specific capacity of 4200mAh / g, and has the advantages of abundant sources, environmental friendliness, and strong stability. Therefore, it has great application prospects in the new generation of negative electrode materials. However, silicon particles will expand up to 400% in volume during the continuous insertion / extraction of lithium in the electrode. After a long period of charge and discharge, the silicon particles will gradually shatter and crack and separate from the electrode. At the same time, the SEI film will grow repeatedly on the silicon surface, which will cause the electrode capacity to decay rapidly and reduce the battery's service life and safety.
[0003] In the manufacturing process of lithium-ion batteries, binder is one of the key components. The role of binder is to connect active materials, conductive agents and current collectors together. Although binder accounts for a very small proportion of the composition of the entire silicon negative electrode, this small amount of binder can effectively alleviate the violent expansion of silicon. Therefore, the performance of the binder directly affects the cycle stability, safety and service life of the battery. Traditional binders mostly use organic solvent systems, which cause environmental pollution, insufficient bonding strength, poor compatibility with electrode materials, poor stability and poor electrochemical performance, which limits their further application in lithium-ion batteries.
[0004] Therefore, it is particularly important to develop an acrylonitrile aqueous binder and preparation process for lithium-ion batteries. Summary of the invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide an acrylonitrile aqueous binder for lithium ion batteries and a preparation process, which solves the problems that traditional binders are easy to pollute the environment, have insufficient bonding strength, poor compatibility with electrode materials, poor stability and poor electrochemical performance, which limit their application in lithium ion batteries.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The preparation process of an acrylonitrile aqueous binder for lithium-ion batteries comprises the following steps:
[0008] Step 1: Add 2-chloro-5-nitrotrifluorotoluene, reduced iron powder, hydrochloric acid solution, anhydrous ethanol, anhydrous acetone and deionized water into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir the reaction for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat the mixture to reflux and continue stirring the reaction for 3-4 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, add the filtrate to ice water, then adjust the pH to 8-9 with sodium hydroxide solution, let stand to precipitate, then vacuum filter, place the filter cake in a vacuum drying oven, and dry it at a temperature of 60-65°C for 2-3 hours to obtain intermediate 1;
[0009] Step 2: Add intermediate 1, ethyl acetate and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add N, N-dimethyl-n-octylamine and continue to stir and react for 10-15 minutes, then heat to reflux and continue to stir and react for 20-30 hours, after the reaction is completed, cool the reaction product to room temperature, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 3-5 hours to obtain intermediate 2;
[0010] Step 3: Add acrylonitrile, itaconic acid, azobisisobutyronitrile, sodium dodecylbenzenesulfonate and cyclohexane to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add calcium chloride solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the addition is completed, the temperature is raised to 70-75°C and the stirring reaction is continued for 6-7 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 50-55°C for 6-8 hours to obtain intermediate 3;
[0011] Step 4: Add intermediate 3, intermediate 2 and anhydrous methanol to a three-necked flask equipped with an agitator, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 8-9 with sodium hydroxide solution, then raise the temperature to reflux and continue stirring the reaction for 10-15 hours, after the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with distilled water 3-5 times, then place in a vacuum drying oven, and dry at a temperature of 60-65°C for 5-7 hours to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0012] As a further scheme of the present invention: the usage ratio of the 2-chloro-5-nitrotrifluorotoluene, reduced iron powder, hydrochloric acid solution, anhydrous ethanol, anhydrous acetone and deionized water in step 1 is 1g:3-5g:1-2mL:10-15mL:10-15mL:5-7mL.
[0013] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step 1 is 36-38%, and the mass fraction of the sodium hydroxide solution is 20-25%.
[0014] As a further scheme of the present invention: the usage ratio of the intermediate 1, ethyl acetate, anhydrous ethanol and N,N-dimethyl-n-octylamine in step 2 is 10 mmol:40-50 mL:40-50 mL:10 mmol.
[0015] As a further scheme of the present invention: the usage ratio of acrylonitrile, itaconic acid, azobisisobutyronitrile, sodium dodecylbenzenesulfonate, cyclohexane and calcium chloride solution in step three is 100 mmol: 5-30 mmol: 0.24-0.48 g: 0.11-0.19 g: 20-30 mL: 80-100 mL.
[0016] As a further solution of the present invention: the mass fraction of the calcium chloride solution in step 3 is 0.5-0.9%.
[0017] As a further solution of the present invention: the usage ratio of the intermediate 3, intermediate 2 and anhydrous methanol in step 4 is 10g:1.5-4.5g:60-80mL.
[0018] As a further solution of the present invention: the mass fraction of the sodium hydroxide solution in step 4 is 15-20%.
[0019] As a further solution of the present invention: the acrylonitrile aqueous binder for lithium ion batteries is prepared according to the preparation process of the acrylonitrile aqueous binder for lithium ion batteries.
[0020] Beneficial effects of the present invention:
[0021] The invention discloses an acrylonitrile water-based binder for lithium ion batteries and a preparation process thereof. The invention uses 2-chloro-5-nitrotrifluorotoluene as a raw material, reduces the nitro group on the 2-chloro-5-nitrotrifluorotoluene to an amino group under the reducing action of reduced iron powder to obtain an intermediate 1, then reacts the intermediate 1 with N,N-dimethyl-n-octylamine, the chlorine atom on the intermediate 1 reacts with the tertiary amine group on the N,N-dimethyl-n-octylamine to form a quaternary ammonium group to obtain an intermediate 2, then copolymerizes acrylonitrile and itaconic acid as polymerization monomers to form polyacrylonitrile modified with a large number of carboxyl groups to obtain an intermediate 3, finally reacts the intermediate 3 with the intermediate 2, the carboxyl group on the intermediate 3 reacts with the amino group on the intermediate 2 to form an amide group, and obtains the acrylonitrile water-based binder for lithium ion batteries. The acrylonitrile water-based binder contains a large number of carboxyl groups and amide groups in its molecular structure, and the presence of a large number of strong polar groups can improve the binder's S i affinity, thereby improving the bonding performance, avoiding bonding failure caused by excessive volume change of Si, ensuring the long-term integrity of the negative electrode sheet of the lithium ion battery, and improving its chemical cycle stability. At the same time, the molecular structure of the acrylonitrile aqueous binder also contains a large number of CF bonds, and the CF bonds have excellent chemical stability and thermal stability, which can further improve the chemical cycle stability of the negative electrode sheet of the lithium ion battery. In addition, the molecular structure of the acrylonitrile aqueous binder also contains a large number of quaternary ammonium groups. The presence of quaternary ammonium groups can promote the rapid migration of lithium ions, greatly improve the charge carrier transport capacity, and thus greatly improve the electrochemical performance of the negative electrode sheet of the lithium ion battery. In addition, the quaternary ammonium groups can interact with the anions in the electrolyte to promote the formation of the SEI film, thereby improving its protective effect on the negative electrode sheet of the lithium ion battery, and can further improve the chemical cycle stability of the negative electrode sheet of the lithium ion battery;
[0022] In summary, the acrylonitrile aqueous binder for lithium ion batteries and the preparation process of the present invention improve the bonding force between the binder and the electrode material, enhance the mechanical strength and stability of the electrode, and improve the conductivity and electrochemical properties of the electrode by introducing trifluoromethyl, quaternary ammonium groups and amide groups, thereby improving the charge and discharge performance, cycle life and rate performance of the lithium ion battery, improving the overall performance of the lithium ion battery, and promoting the sustainable development of the lithium ion battery industry. In addition, the acrylonitrile aqueous binder adopts an aqueous system, does not contain an organic solvent, and is more environmentally friendly. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] This embodiment is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0026] Step 1: 1 g of 2-chloro-5-nitrotrifluorotoluene, 3 g of reduced iron powder, 1 mL of 36% hydrochloric acid solution, 10 mL of anhydrous ethanol, 10 mL of anhydrous acetone and 5 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 10 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then the mixture was heated to reflux and continued to stir for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was added to ice water, and then the pH was adjusted to 8 with a 20% sodium hydroxide solution, and the precipitate was allowed to stand, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain an intermediate 1;
[0027] Step 2: 10 mmol of intermediate 1, 40 mL of ethyl acetate and 40 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 25°C and a stirring rate of 300 r / min for 30 min, and then 10 mmol of N, N-dimethyl-n-octylamine was added and the stirring reaction was continued for 10 min. The mixture was then heated to reflux and the stirring reaction was continued for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at 60°C for 3 h to obtain intermediate 2;
[0028] Step 3: 100 mmol acrylonitrile, 5 mmol itaconic acid, 0.24 g azobisisobutyronitrile, 0.11 g sodium dodecylbenzenesulfonate and 20 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min, and then 80 mL of a 0.5% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 70 ° C and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 50 ° C for 6 h to obtain intermediate 3;
[0029] Step 4: Add 10g of intermediate 3, 1.5g of intermediate 2 and 60mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 30min at a temperature of 25°C and a stirring rate of 300r / min, then adjust the pH to 8 with a 15% mass fraction of sodium hydroxide solution, then heat the mixture to reflux and continue stirring the reaction for 10h. After the reaction, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash it with distilled water 3 times, then place it in a vacuum drying oven, and dry it at a temperature of 60°C for 5h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0030] Embodiment 2:
[0031] This embodiment is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0032] Step 1: 1 g 2-chloro-5-nitrotrifluorotoluene, 4 g reduced iron powder, 1.5 mL of 37% hydrochloric acid solution, 12 mL of anhydrous ethanol, 12 mL of anhydrous acetone and 6 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 12 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then the mixture was heated to reflux and continued to stir for 3.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was added to ice water, and then the pH was adjusted to 8.5 with a 22% sodium hydroxide solution, and the precipitate was allowed to stand, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 62 ° C for 2.5 h to obtain intermediate 1;
[0033] Step 2: 10 mmol of intermediate 1, 45 mL of ethyl acetate and 45 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 28°C and a stirring rate of 350 r / min for 35 minutes, and then 10 mmol of N, N-dimethyl-n-octylamine was added and the stirring reaction was continued for 12 minutes. The mixture was then heated to reflux and the stirring reaction was continued for 25 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at 62°C for 4 hours to obtain intermediate 2;
[0034] Step 3: 100 mmol acrylonitrile, 17 mmol itaconic acid, 0.36 g azobisisobutyronitrile, 0.15 g sodium dodecylbenzenesulfonate and 25 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then 90 mL of a 0.7% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 72 ° C and the stirring reaction was continued for 6.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 52 ° C for 7 h to obtain intermediate 3;
[0035] Step 4: Add 10g of intermediate 3, 3g of intermediate 2 and 70mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, and stir the reaction for 35min at a temperature of 28°C and a stirring rate of 350r / min. Then, adjust the pH to 8.5 with a sodium hydroxide solution with a mass fraction of 18%, and then raise the temperature to reflux and continue stirring the reaction for 12h. After the reaction, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 62°C for 6h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0036] Embodiment 3:
[0037] This embodiment is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0038] Step 1: 1 g of 2-chloro-5-nitrotrifluorotoluene, 5 g of reduced iron powder, 2 mL of 38% hydrochloric acid solution, 15 mL of anhydrous ethanol, 15 mL of anhydrous acetone and 7 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to reflux and continued to stir for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was added to ice water, and then the pH was adjusted to 9 with a 25% sodium hydroxide solution, and the precipitate was allowed to stand, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain intermediate 1;
[0039] Step 2: 10 mmol of intermediate 1, 50 mL of ethyl acetate and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 30°C and 400 r / min for 40 min, and then 10 mmol of N, N-dimethyl-n-octylamine was added and the stirring reaction was continued for 15 min. The mixture was then heated to reflux and the stirring reaction was continued for 30 h. After the reaction was completed, the reaction product was cooled to room temperature, and then placed in a vacuum drying oven and dried at 65°C for 5 h to obtain intermediate 2;
[0040] Step 3: 100 mmol acrylonitrile, 30 mmol itaconic acid, 0.48 g azobisisobutyronitrile, 0.19 g sodium dodecylbenzenesulfonate and 30 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then 100 mL of a 0.9% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to 2 drops / s. After the addition was completed, the temperature was raised to 75 ° C and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 55 ° C for 8 h to obtain intermediate 3;
[0041] Step 4: Add 10g of intermediate 3, 4.5g of intermediate 2 and 80mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 40min at a temperature of 30°C and a stirring rate of 400r / min, then adjust the pH to 9 with a 20% mass fraction of sodium hydroxide solution, then raise the temperature to reflux and continue stirring the reaction for 15h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 65°C for 7h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0042] Comparative Example 1:
[0043] This comparative example is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0044] 100 mmol acrylonitrile, 0.48 g azobisisobutyronitrile, 0.19 g sodium dodecylbenzenesulfonate and 30 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for reaction for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 100 mL of a 0.9% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the temperature was raised to 75° C. and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 55° C. for 8 h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0045] Comparative Example 2:
[0046] This comparative example is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0047] 100 mmol acrylonitrile, 30 mmol itaconic acid, 0.48 g azobisisobutyronitrile, 0.19 g sodium dodecylbenzenesulfonate and 30 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for reaction for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 100 mL of a 0.9% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the temperature was raised to 75° C. and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 55° C. for 8 h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0048] Comparative Example 3:
[0049] This comparative example is a preparation process of an acrylonitrile aqueous binder for lithium ion batteries, comprising the following steps:
[0050] Step 1: 1 g of 2-chloro-5-nitrotrifluorotoluene, 5 g of reduced iron powder, 2 mL of 38% hydrochloric acid solution, 15 mL of anhydrous ethanol, 15 mL of anhydrous acetone and 7 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to reflux and continued to stir for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was added to ice water, and then the pH was adjusted to 9 with a 25% sodium hydroxide solution, and the precipitate was allowed to stand, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain intermediate 1;
[0051] Step 2: 100 mmol acrylonitrile, 30 mmol itaconic acid, 0.48 g azobisisobutyronitrile, 0.19 g sodium dodecylbenzenesulfonate and 30 mL cyclohexane were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then 100 mL of a 0.9% calcium chloride solution was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the temperature was raised to 75 ° C and the stirring reaction was continued for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 55 ° C for 8 h to obtain intermediate 3;
[0052] Step 3: Add 10g of intermediate 3, 4.5g of intermediate 1 and 80mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 40min at a temperature of 30°C and a stirring rate of 400r / min, then adjust the pH to 9 with a 20% mass fraction of sodium hydroxide solution, then raise the temperature to reflux and continue stirring the reaction for 15h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 65°C for 7h to obtain an acrylonitrile aqueous binder for lithium ion batteries.
[0053] Silicon powder with a particle size of 100 nm, conductive agent Super P and acrylonitrile aqueous binder for lithium ion batteries from Examples 1-3 and Comparative Examples 1-3 were mixed uniformly in a mass ratio of 6:2:2, and then deionized water was added for grinding to form a slurry, and the slurry was coated on a copper foil with a scraper to a coating thickness of 100 μm, and then placed in a vacuum drying oven and dried at a temperature of 60°C for 24 hours, and then cut into a circular pole piece with a diameter of 14 mm, ensuring that the active material loading in the circular pole piece is 0.85±0.05 mg / cm 2 , obtaining a negative electrode sheet for a lithium-ion battery;
[0054] The positive electrode of lithium-ion battery is a metal lithium sheet;
[0055] The lithium-ion battery electrolyte is Li PF6 with a molar concentration of 1 mol / L dissolved in a mixed solvent of ethyl carbonate, diethyl carbonate and methyl carbonate in a volume ratio of 1:1:1;
[0056] The lithium-ion battery separator is Celgard 2320 lithium battery separator.
[0057] The lithium-ion battery negative electrode sheet, the lithium-ion battery positive electrode sheet, the lithium-ion battery electrolyte and the lithium-ion battery separator were assembled into a CR2025 button half-cell in a glove box, and sealed with a sealing machine at a pressure of 50MPa. After standing for 24 hours, the cells were activated for 3 cycles at a current density of 0.5A / g, and their discharge capacity was tested to obtain the first discharge capacity. After that, the cells were cycled for 100 cycles at a current density of 4A / g, and their discharge capacity was tested to obtain the second discharge capacity. The test results are shown below:
[0058]
[0059] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the acrylonitrile aqueous binder for lithium ion batteries in the present invention has excellent electrochemical performance and chemical cycle stability.
[0060] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A process for preparing an acrylonitrile aqueous binder for lithium ion batteries, characterized in that: The following steps are involved: Step 1: Add 2-chloro-5-nitrotrifluorotoluene, reduced iron powder, hydrochloric acid solution, anhydrous ethanol, anhydrous acetone and deionized water into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir the reaction for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat the mixture to reflux and continue stirring the reaction for 3-4 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, add the filtrate to ice water, then adjust the pH to 8-9 with sodium hydroxide solution, let stand to precipitate, then vacuum filter, place the filter cake in a vacuum drying oven, and dry it at a temperature of 60-65°C for 2-3 hours to obtain intermediate 1; Step 2: Add intermediate 1, ethyl acetate and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add N, N-dimethyl-n-octylamine and continue to stir and react for 10-15 minutes, then heat to reflux and continue to stir and react for 20-30 hours, after the reaction is completed, cool the reaction product to room temperature, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 3-5 hours to obtain intermediate 2; Step 3: Add acrylonitrile, itaconic acid, azobisisobutyronitrile, sodium dodecylbenzenesulfonate and cyclohexane to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add calcium chloride solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the addition is completed, the temperature is raised to 70-75°C and the stirring reaction is continued for 6-7 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 50-55°C for 6-8 hours to obtain intermediate 3; Step 4: Add intermediate 3, intermediate 2 and anhydrous methanol to a three-necked flask equipped with an agitator, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 8-9 with sodium hydroxide solution, then raise the temperature to reflux and continue stirring the reaction for 10-15 hours, after the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with distilled water 3-5 times, then place in a vacuum drying oven, and dry at a temperature of 60-65°C for 5-7 hours to obtain an acrylonitrile aqueous binder for lithium ion batteries.
2. The process for preparing an aqueous acrylonitrile binder for lithium ion batteries according to claim 1, characterized in that: The dosage ratio of the 2-chloro-5-nitrotrifluorotoluene, reduced iron powder, hydrochloric acid solution, anhydrous ethanol, anhydrous acetone and deionized water in step 1 is 1g:3-5g:1-2mL:10-15mL:10-15mL:5-7mL.
3. The process for preparing an aqueous acrylonitrile binder for lithium ion batteries according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution in step 1 is 36-38%, and the mass fraction of the sodium hydroxide solution is 20-25%.
4. The process for preparing an aqueous acrylonitrile binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the intermediate 1, ethyl acetate, anhydrous ethanol and N,N-dimethyl-n-octylamine in step 2 is 10 mmol:40-50 mL:40-50 mL:10 mmol.
5. The process for preparing the acrylonitrile aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the acrylonitrile, itaconic acid, azobisisobutyronitrile, sodium dodecylbenzenesulfonate, cyclohexane and calcium chloride solution in step 3 is 100mmol:5-30mmo l:0.24-0.48g:0.11-0.19g:20-30mL:80-100mL.
6. The process for preparing an acrylonitrile aqueous binder for lithium ion batteries according to claim 1, characterized in that: The mass fraction of the calcium chloride solution in step 3 is 0.5-0.9%.
7. The process for preparing an acrylonitrile aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the intermediate 3, intermediate 2 and anhydrous methanol in step 4 is 10g:1.5-4.5g:60-80mL.
8. The process for preparing an aqueous acrylonitrile binder for lithium ion batteries according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution in step 4 is 15-20%.
9. An acrylonitrile aqueous binder for lithium ion batteries, characterized in that: The acrylonitrile aqueous binder for lithium ion batteries is prepared according to the preparation process of the acrylonitrile aqueous binder for lithium ion batteries according to any one of claims 1 to 8.
Citation Information
Patent Citations
High-performance binder for silicon materials for lithium ion batteries and preparation method thereof
CN104538635A
Aqueous binder for lithium ion battery negative electrode and preparation method of the same
JP2017174804A